DIFFERENCES IN TEACHING ENGLISH TO YOUNG LEARNERS AND ADULTS - Umarova Dilshoda, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation (English): This article examines the differences between teaching English to young learners and adults. It explores how age influences learning styles, motivation, classroom behavior, and teaching methods. Young learners benefit more from interactive, playful, and emotionally engaging activities, while adults prefer structured explanations, goal-oriented tasks, and practical communication. Based on established ELT literature, the article highlights the importance of adapting teaching strategies to learners’ developmental and psychological needs in order to ensure effective language acquisition.